2010
DOI: 10.1177/0310057x1003800112
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl dose for the Insertion of Classic™ Laryngeal Mask Airways in Non-Paralysed Patients Induced with Propofol 2.5 mg/kg

Abstract: The aim of this randomised, controlled trial was to determine the optimum dose of fentanyl in combination with propofol 2.5 mg.kg-1 when inserting the Classic™ Laryngeal Mask Airway. Seventy-five ASA I or II patients were randomly assigned to five groups of fentanyl dosage: 0 µg.kg-1 (placebo), 0.5 µg.kg-1 , 1.0 µg.kg-1 , 1.5 µg.kg-1 and 2.0 µg.kg-1. Anaesthesia was induced by first injecting the study drug over 10 seconds. Three minutes after the study drug was injected, propofol (2.5 mg.kg-1) was injected ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[67] Tan and Wang have shown that fentanyl increases the incidence of prolonged apnea in a dose-dependent manner. [16] Dexmedetomidine itself lacks respiratory depressant effect, and has shown to cause significant increase in RR during its infusion due to its action at multiple sites including locus ceruleus, pulmonary vasculature, and carotid body by stimulating respiratory center. [17] Apnea occurring in few patients in PD group may be due to the effect of 2.5 mg/kg of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…[67] Tan and Wang have shown that fentanyl increases the incidence of prolonged apnea in a dose-dependent manner. [16] Dexmedetomidine itself lacks respiratory depressant effect, and has shown to cause significant increase in RR during its infusion due to its action at multiple sites including locus ceruleus, pulmonary vasculature, and carotid body by stimulating respiratory center. [17] Apnea occurring in few patients in PD group may be due to the effect of 2.5 mg/kg of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…The predetermined dose of propofol induction (2 mg/kg) along with the timing of administering propofol injection and i-gel ® insertion after pre-treatment with fentanyl or dexmedetomidine, were as suggested by previous researchers. [619202122] The aim was to achieve effective synergistic levels of the drug combinations used before I gel insertion.…”
Section: Discussionmentioning
confidence: 99%